2020
DOI: 10.1159/000506434
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Pre-Moxibustion on Reproductive Hormones Profile of Rats with <b><i>Tripterygium</i></b> Glycosides-Induced Ovarian Damage

Abstract: Background: Acupuncture and moxibustion have been proven to be conducive to improving the ovarian reserve. However, the mechanism of pre-moxibustion on Tripterygium glycosides (TG)-induced ovarian damage has not been previously reported. Method: Female rats were randomly divided into 5 groups: control, model (75 mg/kg TG, 14 days), preventive moxibustion 1 (PM1, receiving moxibustion for 4 weeks before TG administration), preventive moxibustion 2 (PM2, receiving moxibustion for 2 weeks before TG administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It uses Folium Artemisiae argyi to produce moxibustion materials, generating heat upon combustion to stimulate acupoints or specific body surface sites, thereby achieving disease prevention and treatment. Increasing evidence has demonstrated that moxibustion is able to improve ovarian function (8)(9)(10)(11)(12). It has been reported that the early use of moxibustion is able to generate a favorable stress response to resist or reduce the subsequent disease and delay the degradation of normal tissues (13).…”
Section: Introductionmentioning
confidence: 99%
“…It uses Folium Artemisiae argyi to produce moxibustion materials, generating heat upon combustion to stimulate acupoints or specific body surface sites, thereby achieving disease prevention and treatment. Increasing evidence has demonstrated that moxibustion is able to improve ovarian function (8)(9)(10)(11)(12). It has been reported that the early use of moxibustion is able to generate a favorable stress response to resist or reduce the subsequent disease and delay the degradation of normal tissues (13).…”
Section: Introductionmentioning
confidence: 99%
“…ODs are an important cause of infertility [20], with a considerable impact on the psychological health of the women affected as well as on their familial relationships. The wide application of acupuncture and moxibustion in clinical practice leaded to a rapid expansion of the research on their effects in the treatment of ODs [21,22,23,24]. The therapeutic results of complementary and alternative medicine are promising.…”
Section: Discussionmentioning
confidence: 99%
“…EA improved PCOS-IR by down-regulating hypothalamic NFκB protein expression and significantly reduced abdominal circumference, body weight, serum fasting glucose, fasting insulin, and IR in rats [83]. Zhu et al [84] found that moxibustion could rescue the HPO axis of ovarian-injured rats, improve hypothalamic GnRH mRNA overexpression and abnormal secretion of reproductive hormones, and maintain normal ovarian function. Huang et al [85] found that EA could activate the PI3K/AKT signaling pathway, inhibit autophagy-induced follicular atresia, and reduce serum T, LH, and anti-müllerian hormone (AMH) levels, thus improving ovulation.…”
Section: Regulation Of Hpoa Function Modern Studies Havementioning
confidence: 99%